Drainage Analysis of Pondok Jati Housing and Drainage Replanning - Fathurokman, Hasan Alif; Wulandari, Esti; Laksono Djoko (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2025)
The Pondok Jati housing complex is less able to receive or accommodate rainwater discharge due to changes in channel dimensions, shallowing of channels, and dirt due to waste from people who do not care about the local environment. To anticipate this, it is necessary to repair and build infrastructure that functions as a flood controller according to the characteristics and conditions of the location. Efforts made for this are to redesign drainage at low cost. Hydrology and Hydraulics methods are applied to obtain a 5-year planned discharge and existing channel discharge, to plan channels with a 5-year planned return period. The existing channel discharge for the Pondok Jati housing complex is obtained as much as 0.450 m3/sec, and modeling is carried out in accordance with SNI 02-2406-1991: Procedures for general planning of urban drainage. With the redesign, the planned channel dimensions are obtained measuring 0.50 m x 0.75 m, in the form of a square without a cover.